The ethical limits of bungee research in ICTD - Dearden, Andrew; Tucker, William D. (2015 IEEE International Symposium on Technology and Society, 2015)
Research in ICTD is difficult because engineers with technical experti se are separated from the challenges that they are trying to address b y large physical distances and significant social differences. To over come these challenges, much research involves occasional short visits by external researchers to developing regions to investigate problems and generate ideas which are then developed back at the engineers' hom e base before further return visits for deployment and evaluation. Thi s paper highlights the ethical limitations of this `bungee research', and reflects on our experiences in evolving more fruitful research pra ctices. We argue that relying on bungee research as a primary model of research engagement is unethical, and we suggest some minimal conditi ons that are necessary, but not sufficient, for such visits to be ethi cally defensible in ICTD research.